Comparative studies in economic crime: old behaviours, new challenges (REVISTA BRASILEIRA DE EXECUÇÃO PENAL, 2021)
In consideration to the theoretical approach on the economics of crime, our study aims to contribute to the understanding of crime based on primary data obtained through the application of questionnaires/interviews with convicted people, who committed economic crimes (drug trafficking, robbery, among others). This empirical evidence was obtained from three different pieces of research: 1st) of convicted people in penal establishments in Paraná and Rio Grande do Sul; 2nd) of convicted people in the scope of the 4th Federal Court of Foz do Iguaçu (Paraná), whose criminal sentences have been replaced by community service or pecuniary sanctions; 3rd) of jailed women in the Rio Branco Women’s Prison (Acre). As a result, for a significant percentage of the 670 people surveyed in the three pieces of research, the economic returns were, on average, higher than the costs of crime, meaning that crime is worth it.
Keywords: Cost-benefit relationship. Rational.ity. Criminality